Enhancing Biocide Safety of Milk Using Biosensors Based on Cholinesterase Inhibition - Lynn Mouawad; Georges Istamboulie; Gaëlle Catanante; Thierry Noguer (Biosensors)
A sensitive and reliable electrochemical biosensor for the detection of benzalkonium chloride (BAC) and didecyldimethylammonium chloride (DDAC), the most commonly used disinfectant biocides in the agri-food industry, is described. Acetylcholinesterase from Drosophila melanogaster (DM AChE) and butyrylcholinesterase from horse serum (BChE) were immobilized by entrapment in a photocrosslinkable polymer on the surface of carbon screen-printed electrodes. Preliminary tests conducted in phosphate buffer showed limits of detection (LODs) of 0.26 µM for BAC using the BChE-based sensor and 0.04 µM for DDAC using the DM AChE sensor. These performances comply with the European regulation for dairy products, which sets a maximum allowable concentration of 0.28 µM for biocides. However, when tested directly in milk samples, a dramatic decrease in the sensitivity of both sensors towards BAC and DDAC biocides was reported. To overcome this problem, a simple liquid–liquid extraction was necessary prior to biosensor measurements, ensuring that the biosensors met European regulatory standards and provided an unbiased response.